Neuropsychological functions of nonverbal hand movements and gestures during sports. Issue 3 (3rd April 2022) - Neumann, N.; Drewes, V.; Konstantinidis, I.; Reinecke, K. H. C.; Lausberg, H.; Helmich, I.
ABSTRACT: Emotional body-distant gestures are a prominent feature of winning athletes. Because negative emotions have been associated to increased self-touch behaviour, we investigated the hypothesis that athletes change from a more body-distant nonverbal hand movement behaviour when winning to a body-focused behaviour when losing. Nonverbal hand movements of professional right-handed tennis athletes were video-taped during competition and analyzed by certified raters using the NEUROpsychological GESture(NEUROGES)System. The results showed that losing athletes increase their irregular, on body, and phasic on body hand movements, particularly with the left hand. Emotion / attitude rise gestures with the right hand characterised winning athletes. The data suggest that the nonverbal hand movements of athletes serve different neuropsychological functions. Winners nonverbally express their positive feelings by body-distant gestures but change towards their own body to regulate stress when losing. Highlights Irregular, on body, and phasic on body hand movements serve self-regulation when losing during competition Athletes express positive emotions by emotion / attitude rise gestures Nonverbal expression of emotions underlie hemispherically lateralised processes